O diálogo na relação professor-alunos: a complexa trama das interações no cotidiano da aula no ensino médio - Camargo, Alessandra Ferreira de (2017)
The human being is constituted in interaction, with the other and to the other, which involves the exchange of statements, gestures, looks and meaning. School is, by excellence, a space of secondary socialization whereby the subjects interact and are inserted in the forms of the current culture. The complex interaction between teachers and students, taken as an object in this research, is fundamental and structuring axis of the school. The notions of Bakhtin and the Circle about the language were relevant to the analytical approach of the theme , since they affirm the importance of the statements in the constitution of the subjects as social beings, one of the main functions of the school. Thus, based on the bakhtinian notions, the research exposed by this dissertation aimed to investigate which enunciative devices are mobilized in the interactions in the classroom, and how they favor or restrict the dialogue between teacher and students. It was realized an ethnographic case study and data were produced through classroom observations, focus group and interview, using video recordings and field journal. The selected subject group was integrated by a teacher of the Language Area of a state public school and her students of the second year of High School, day and night shift class, of a municipality in the northern region of the state of Rio Grande do Sul. After reading and analyzing all the material produced, thematic categories were drawn from the topics and singularities of the material and, from these themes, scenes from the class room observations were selected together with excerpts from the focus group and excerpts from the interview with the teacher, in order to make a study of the material with the Bakhtinian theoretical basis and using as methodology of analysis the Dialogical Analysis of the Discourse (ADD) . The thematic categories that emerged from the material were the presence of culture in the classroom, the power play in the pedagogical relationship, the use of questions by the teacher, the use of humor and irony in verbal interactions. Based on the analysis of the material, it was verified that the devices of active responsive comprehension, alterity listening and opening to the multiplicity of voices were the most present in the observed scenes and excerpts. All interaction is dialogic, but at times, this dialogicity is expressed more explicitly. In the statements in which the explicit mobilization of the enunciative devices was identified, there was a more productive interaction, which favored the quality of the dialogues established. There was a re-signification of the researcher's teaching practice, abandoning the search for consensuses and opening spaces for the multiplicity of voices in class. Finally, the study concludes that the activation of enunciative devices may rather contribute to a more satisfactory interaction between teacher-students, but for the use of such devices to come from theoretical principles and not just from intuition, it is important and necessary for the teacher to reflect about his conceptions of dialogue and about his own actions in the dialogue with the students.